Philology and Music in the Work of Pascal Quignard - John Hamilton (Studies in 20th & 21st Century Literature, 2009)
The persistent association of philology and music in the work of Pascal Quignard is mediated through various modalities of silence. Throughout Quignard’s novels, essays and treatises, musical sensibility and philological obsession work to silence the all-too-loud, abstracting processes of communication, representation, narration, or discourse. Upon sketching out the general terms and definitions that Quignard employs across his writing career, the essay turns to two especially illustrative examples: Quignard’s reading of Lucretius and his reflections on Plato’s discussion of misology. Misology, denoting a deep mistrust of words, ends up serving as a synonym for philology itself; it is a hatred of words—that is, a hatred of the way words are subsumed into logical discourse—that presents itself as the only true love of words, a love that respects a word’s resistance to any system, a philology that attends to a word’s relation to silence and thereby to the music of singularity.
Keywords: philology; music; Pascal Quignard; silence; misology; singularity